The daf-7(e1372) mutation rescues dauer formation defects seen in C. elegans unc-33 mutants - Samaro, Alexia; Cristancho, Alejandra; Rivas, Alexis; Valtierra, Ruby; Beck, Skye; Cantu, Jason; Miranda, Maria; Vacio, Arianna; Cardenas Muedano, Oscar; Holgado, Andrea (Frontiers in Physiology, 2023)
Collapsin response mediator protein-2 (CRMP2) in humans, UNC-33 in C. elegans, is a molecule that mediates axonal outgrowth and stability. UNC-33/CRMP2 has been hypothesized as a potential drug target for treating Alzheimer’s and other neurodegenerative diseases, which can often be attributed in part to aging. In aging, CRMP2 becomes hyperphosphorylated, which decreases the protein's functionality, destabilizes the cellular skeleton, and leads to neurodegeneration. In C. elegans, aging can be slowed by entering dauer diapause; a non-aging developmental stage turned on when the DAF-7/TGFβ signaling pathway is silenced in response to environmental stressors. In our laboratory, we discovered that unc-33 mutants are unable to form dauers in response to environmental stressors, but the mechanism behind this is still unknown. Here, we present a study that investigates whether a mutation in the daf-7 gene can rescue phenotypes characteristic of unc-33 mutants. To this end, we created unc-33; daf-7 double mutants and quantified proper dauer formation after exposure to unfavorable environmental conditions. In addition, we tested how the introduction of the daf-7 mutation would affect the locomotion of the double mutants on an agar plate and a liquid medium. Furthermore, we examined axonal elongation of the double mutants using a transgene, juIs76, which expresses GFP in GABAergic motor neurons. Our analysis of unc-33; daf-7 double mutants showed that introducing the daf-7 mutation into an unc-33 mutant rescued dauer formation. However, further studies revealed that the double mutants still had the unc-33 mutant defects in axonal outgrowth and locomotion. Based on these results, we concluded that unc-33 mutants might have a problem suppressing DAF-7 signaling under unfavorable environmental conditions, leading to the activation of reproductive programs and the development of adults instead of dauers.